2019
DOI: 10.1111/ppa.13080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma viride pre‐inoculation in pine species with different levels of susceptibility to Fusarium circinatum: physiological and hormonal responses

Abstract: Pine pitch canker (PPC), caused by Fusarium circinatum, affects Pinus species worldwide. Although no effective solutions have yet been found to control it, there is a growing interest in using biological control agents (BCA) such as Trichoderma to avoid the application of chemical‐based products. Using species with an increasing level of susceptibility to PPC (Pinus pinea, Pinus pinaster and Pinus radiata), this study aimed to evaluate the effect of Trichoderma viride pre‐inoculation on disease development, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…In these studies, the manipulation of susceptible hosts by F. circinatum showed to disturb ethylene homeostasis, block jasmonic acid (JA) signalling and arrest salicylic acid biosynthesis. The role of JA regulation in PPC has been also discussed based on hormone quantification data (Amaral et al 2019a(Amaral et al , 2019bCerqueira et al 2017), as well as the importance of abscisic acid (ABA) biosynthesis and catabolism in determining pine resistance/susceptibility to PPC (Amaral et al 2020a).…”
mentioning
confidence: 99%
“…In these studies, the manipulation of susceptible hosts by F. circinatum showed to disturb ethylene homeostasis, block jasmonic acid (JA) signalling and arrest salicylic acid biosynthesis. The role of JA regulation in PPC has been also discussed based on hormone quantification data (Amaral et al 2019a(Amaral et al , 2019bCerqueira et al 2017), as well as the importance of abscisic acid (ABA) biosynthesis and catabolism in determining pine resistance/susceptibility to PPC (Amaral et al 2020a).…”
mentioning
confidence: 99%
“…The relationship of F. circinatum with the internal microbiota of seedlings has been poorly described, but some studies have shown that certain fungal endophytes isolated from pines are able to produce an antagonistic effect against F. circinatum [266], reducing the severity of F. circinatum when applied to seedlings as a preventive measure. Other studies have revealed how the exudates obtained from avirulent strains of a plant pathogen, living as an endophyte, induce systemic resistance against the virulent strain of the same pathogenic species [272]. Thus, the study of this relationship may reveal potential strategies for the biological control of PPC disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, several aspects, such as the application timing in biological control agents, should be taken into account. Amaral et al [272] demonstrated that T. viride preinoculation accelerated disease progression of PPC. They suggested that T. viride may subvert the plant defence mechanisms for successful root colonization, which would facilitate F. circinatum infestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCAs that target F. circinatum have gained considerable support in recent research and were recently reviewed in Martín-García et al [143]. In general, the control of woody plant diseases using BCAs is highly context dependent [165,166] and pathogen-specific but it seems to be more effective when applied as a preventive treatment [142,[167][168][169].…”
Section: Good Nursery Practicesmentioning
confidence: 99%